Seismic Crustal and Upper Mantle Structure of Iraq and Surrounding Regions Inferred from Regional Waveform Inversions - Aleqabi, Ghassan I.; Ghalib, Hafidh A. A.; Wysession, Michael E. (Sulaimani Journal for Pure and Applied Sciences, 2016)
The shear wave (S-wave) velocity structure of the crust and its effect on seismic-wave propagation are of fundamental interest in many geophysical studies. S-wave velocities and layer thicknesses have a dominating influence on the waveforms of Rayleigh waves. Rayleigh wave waveforms from the Northern Iraq Seismographic Network (NISN) are inverted to constrain the crustal and upper mantle velocity structure in Iraq and surrounding regions. The inversion uses a niching genetic algorithm (NGA), which optimizes four parameters of earth properties at different frequencies and in different sub-populations: P-wave velocity, S-wave velocity, density, and Earth layer thicknesses. Each subpopulation separately performs the genetic algorithm processes of selection, crossover, and mutation of the velocity models, with the niching function removing models that are too similar to maintain distinct subpopulations. Using both observed earthquake surface waves waveforms and synthetic forward-modeled waveforms; we obtain regional S-wave profiles for the crust (including top-most sedimentary layers), and the upper mantle. We demonstrate that the NGA method is a robust means of interpreting observed surface-wave waveform data.
Keywords: waveformmatchinggeneticalgorithmniching